(untitled) (African Journal of Biomedical Research, 2024)
The knowledge of mental health in adolescents is essential because it empowers them with the skills to build better lives, positive attitudes, better systems of care and better society. In most societies today, mental illness has become a global problem, affecting people of all ages at any given point in time. And poor knowledge of mental illness has led to negative attitude towards mental illness and people living with it in different communities and has contributed to low treatment seeking and stigmatization of people with mental illness. This study was aimed at assessing the knowledge and attitude towards mental illness among in-school adolescents. A descriptive survey design was used for the study. Using a multi stage sampling procedure, two secondary schools in Enugu were randomly (balloting) selected for the study. Simple random sampling method was used to select a sample of 140 in-school adolescent students aged 15-19 years who met the inclusion criteria was used. Data was collected using the validated Disposition towards Mental Illness Scale to determine the adolescents’ level of knowledge of mental illness and attitude towards mental illness. The overall level of knowledge of mental illness among in-school adolescents was generally low (42.1%) and the overall attitude towards mental illness was high and positive (71.3%). There is need to improve the knowledge of mental health and mental illness among adolescents for proper psychosocial development and improved mental wellbeing